Molecular Analysis of Dichelobacter Nodosus Isolated From Footrot Infected Sheep in Malaysia - Zakaria, Zunita (2001)
Footrot has become an increasingly important disease of sheep in Malaysia. Therefore, the molecular analysis of the causative agent of footrot, Dichelobader nodosus isolated from footrot infected sheep was undertaken. Fifteen D. nodosus isolates were recovered from 38 sheep showing clinical signs of footrot in two government sheep farms located approximately 200km apart The isolates were studied and results analysed. Preliminary identification of the organism was carried out by the Gram-stain method while the polymerase chain reaction (PCR) method using species-specific primers, A and Ac, was employed for species confirmation. All 15 isolates produced a single product of approximately 780 basepairs. Although obtained from two different locations, all isolates were found to be of serogroup B. Two conventional methods, namely the elastase and gelatingel tests, were used to assess the virulence of the isolates. Generally, the isolates exhibited variations in the laboratory characteristics. Based on the virulence assessment, some of the isolates appeared to have the capability for causing virulent footrot but were isolated from sheep that did not show clinical signs of the virulent form of footrot. This was probably due to the constant topical treatment regime and the vaccination programme practised by the farm management which may have caused the bacteria to not fully express its virulence characteristics. Analysis of the fimbrial subunit gene sequence revealed the local strains had sequences that are distinct from the prototype strains. There were 94 to 97 percent amino acid similarities (identities and conserved changes) between the local isolates and the prototype strains. The expression of D. nodosus fimbriae serotype B2 in an easily grown aerobe, Pseudamonas aeruginosa, were carried out successfully. Dichelobader nodosus fimbrial subunit gene was cloned in an expression vector, pUCpKS downstream the lac promoter to construct the recombinant plasmid pMAL99. Recombinant P. aeruginosa cells containing this construct were able to produce a high yield of fimbriae. The fimbriae were physically, structurally and antigenically indistinguishable from those produced by the D. nodosus isolates from which the fimbrial subunit gene was originally derived. This was shown and confirmed by Western blot analysis. When the fimbriae produced by the P. aeruginosa harbouring pMAL99 were extracted, purified and used as vaccines in sheep, the results conclusively showed that these vaccines were equally effective as either the native whole cells or isolated fimbriae from D. nodosus in eliciting the antibody response. The vaccinated sheep were found protected against homologous serogroup challenge. The recombinant fimbriae also produced crossprotective antibodies to heterologous serotypes B3 and B4 infections. Therefore, the monovalent serogroup specific recombinant vaccine has a good potential for use in farms in this country to protect sheep against footrot.